Lycomimus, a new genus of Australian Ptilodactylidae (Coleoptera: Byrrhoidea) - Lawrence, John F.; Slipinski, Adam (Zootaxa, 2013)
A new genus of Ptilodactylidae, Lycomimus gen. n., based on L. bejsaki sp. n. from northern New South Wales and southern Queensland, Australia, is described. The genus is compared with other known ptilodactylid genera, and a key is provided to the genera occurring in Australia.